SDPR expression in human trabecular meshwork and its potential role in racial disparities of glaucoma - Shui, Ying-Bo; Liu, Ying; Huang, Andrew J. W.; Siegfried, Carla J. (Scientific reports, 2024)
In order to identify how differential gene expression in the trabecular meshwork (TM) contributes to racial disparities of caveolar protein expression, TM dysfunction and development of primary open angle glaucoma (POAG), RNA sequencing was performed to compare TM tissue obtained from White and Black POAG surgical (trabeculectomy) specimens. Healthy donor TM tissue from White and Black donors was analyzed by PCR, qPCR, immunohistochemistry staining, and Western blot to evaluate SDPR (serum deprivation protein response; Cavin 2) and CAV1/CAV2 (Caveolin 1/Caveolin 2). Standard transmission electron microscopy (TEM) and immunogold labeled studies were performed. RNA sequencing demonstrated reduced SDPR expression in TM from Black vs White POAG patients’ surgical specimens, with no significant expression differences in other caveolae-associated genes, confirmed by qPCR analysis. No racial differences in SDPR gene expression were noted in healthy donor tissue by PCR analysis, but there was greater expression as compared to specimens from patients with glaucoma. Analysis of SDPR protein expression confirmed specific expression in the TM regions, but not in adjacent tissues. TEM studies of TM specimens from healthy donors did not demonstrate any racial differences in caveolar morphology, but a significant reduction of caveolae with normal morphology and immuno-gold staining of SDPR were noted in glaucomatous TM as compared to TM from healthy donors. Linkage of SDPR expression levels in TM, POAG development, and caveolar ultrastructural morphology may provide the basis for a novel pathway of exploration of the pathologic mechanisms of glaucoma. Differential gene expression of SDPR in TM from Black vs White subjects with glaucoma may further our understanding of the important public health implications of the racial disparities of this blinding disease.